Harvard business essentials : (Harvard Business School Press, 2004)
Creating Teams with an Edge: The Complete Skill Set to Build Powerful and Influential Teams Teams can be a driving force for organizational performance-and managers can play a key role in teams' ultimate success or failure. Highlighting the latest research on team development and dynamics-and including hands-on tools for improving communication, resolving conflicts, promoting interdependence, and more-this guide will help managers at all levels to motivate teams to achieve higher performance. The Harvard Business Essentials series is for managers at all levels but is especially relevant for new managers. It offers on-the-spot guidance, coaching, and tools on the most relevant topics in business. Each book includes the critical information that managers need on a given topic-from budgeting to hiring to communication to strategy-and offers interactive tools and worksheets that translate advice into action. Providing ready answers to day-to-day issues, these guides make sound, trusted mentoring advice available whenever managers need it. Other Books in the HBE Series: Managing Change and Transition Hiring and Keeping the Best People Finance for Managers Business Communications Innovation Negotiation